Solitary renal metastasis from squamous cell carcinoma of the lung: A case report. Issue 5 (February 2019) - Wang, Jiantao; Wang, Li; Long, Lang; Tao, Qing; Xu, Feng; Luo, Feng
Abstract: Rationale: Non-small cell cancer with isolated unilateral renal metastasis is rare, and the role of radical nephrectomy has not been determined. In the present study, a case of a patient with solitary kidney metastasis from squamous cell lung cancer who underwent radical nephrectomy is reported. Patient concerns: A 74-year-old patient diagnosed with pulmonary squamous cell lung cancer who had undergone radical pulmonary lobectomy and mediastinal lymph node dissection revealed a solitary mass in the right kidney during the follow-up. Diagnoses: Unilateral isolated kidney metastasis originated from squamous cell lung cancer. Interventions: The patient underwent radical right nephrectomy and squamous cell cancer metastasis was confirmed by the postoperative pathology results. Outcome: Lung cancer relapse was diagnosed and the patient died of cancer progression 10 months after the right nephrectomy. Lessons: Solitary renal metastasis is rare and squamous cell lung cancer might be the primary disease. Abdominal computed tomography (CT) is important in detecting solitary kidney metastasis during the follow up of patients with squamous cell lung cancer. Due to the rareness of isolated renal metastasis, the role of radical nephrectomy needs to be further investigated.